Analisis Pengaruh Kinerja Lingkungan, Trade Openness, Dan Jumlah Populasi Terhadap Pertumbuhan Ekonomi Dalam Perspektif Ekonomi Islam (Analisis Data Panel Kawasan ASEAN Tahun 2018-2023) - Junita Aurelia, Nindia; Susanto, Is (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2025)
This study aims to analyze the influence of environmental performance, trade openness, and population growth on economic growth in the ASEAN region in the 2018-2023 period, using an Islamic economic perspective. This study uses secondary data obtained from the World Bank, with analysis carried out by the panel data regression method using the E-Views 12 software. The results of the analysis show that environmental performance has a positive effect on economic growth, trade openness does not have a positive effect on economic growth, and population size has a positive effect on economic growth. Meanwhile, simultaneously or jointly environmental performance, trade openness, and population size affect economic growth. Meanwhile, the integration of Islamic economic principles can promote sustainable and equitable economic growth in the ASEAN region, taking into account environmental, trade, and demographic factors.